2018
DOI: 10.31225/osf.io/b376h
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MR-Guided Focused Ultrasound Ablation of Visceral Fat: A new treatment for metabolic syndrome

Abstract: I am writing to provide you and the Foundation the final report on the execution of the project entitled "MR-Guided Focused Ultrasound Ablation of Visceral Fat: A new treatment for metabolic syndrome". BackgroundThe overarching goal of the research is to develop a non-invasive approach for the treatment of metabolic syndrome. The main hypothesis of the project is that HIFU ablation of visceral fat can improve insulin action in obese rats and provide a non-invasive treatment for type 2 diabetes and other diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Visceral fat and its resident macrophages produce pro-inflammatory cytokines (e.g., necrosis factor-alpha, leptin, and interleukin-6) that are implicated in chronic low-grade inflammation which can subsequently lead to MS in the obese. 25,27,28) Our study observed that VO and overweight were factors that were positively associated with the incidence of each component of MS. In the present study, both SBP and DBP were slightly positively associat-ed with weight compared to VO.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Visceral fat and its resident macrophages produce pro-inflammatory cytokines (e.g., necrosis factor-alpha, leptin, and interleukin-6) that are implicated in chronic low-grade inflammation which can subsequently lead to MS in the obese. 25,27,28) Our study observed that VO and overweight were factors that were positively associated with the incidence of each component of MS. In the present study, both SBP and DBP were slightly positively associat-ed with weight compared to VO.…”
Section: Discussionmentioning
confidence: 54%
“…Previously, obesity-associated MS was considered to be related to the accumulation of visceral fat, rather than subcutaneous fat or total body fat. Visceral fat and its resident macrophages produce pro-inflammatory cytokines (e.g., necrosis factor-alpha, leptin, and interleukin-6) that are implicated in chronic low-grade inflammation which can subsequently lead to MS in the obese [ 25 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%